Wonder and Childhood: Thinking with Wittgenstein and Heidegger about the Connection between Wonder, Childhood and Philosophy - Luca Zanetti (Encyclopaideia)
Starting from Wittgenstein and Heidegger’s remarks on wonder and astonishment, in this article I highlight the difference between relative wonder, which is relative to our temporary ignorance of the causes of phenomena, and absolute wonder, which grasps the existence of the world, and of everything in it, as a miraculous event which is in principle inexplicable. I then highlight how this absolute wonder can also be accompanied with less luminous emotions, such as anguish and horror. If the experience of childhood is characterized by this kind of wonder, then, I argue, it is important to reflect upon its value and the ways in which we can be with children when confronting the fascinating and terrible mystery of existence.